37 Transoesophageal Echocardiography Underestimates Transvalvular Gradients following Trans-Catheter Aortic Valve Implantation (TAVI) – Implications for Clinical Practice. (3rd June 2016) - Solcanova, Andrea; Bates, Sarah; Calver, Alison; Curzen, Nick; Rakhit, Dhrubo; Shah, Benoy
Abstract : Background: Trans-catheter aortic valve implantation (TAVI) is an effective treatment for high risk patients with severe aortic stenosis. As with all prosthetic valves, it is important to document accurate post-procedural gradients for future comparison. This study aimed to determine whether there was a difference between gradients measured immediately post-procedure by trans-oesophageal echocardiography (TOE) compared with the pre-discharge trans-thoracic echocardiogram (TTE). We also compared pre-TAVI gradients obtained by TTE vs. TOE. Methods: We used local and national databases to gather demographics on TAVI patients from our centre and to identify peak and mean aortic gradients measured by TTE and TOE prior to TAVI and also immediately following TAVI deployment (TOE) and prior to discharge (TTE). Data were compared using the paired t-test. Results: We identified 106 TAVI patients with complete echocardiographic data-sets. The mean age was 81+/-8 yrs and 62(54%) were male. All patients received an Edwards Sapien valve. Pre-TAVI, there were no significant differences between TOE and TTE for both peak (72.2+/-24.8 mmHg vs 71.9+/- 24.0 mmHg, p = 0.83) and mean (41.4+/-15.0 mmHg vs 42.4+/-14.9 mmHg, p = 0.22) gradients. However, following TAVI, the peak trans-valvular gradients by TOE vs. TTE were 12+/-6 mmHg vs 22+/-9 mmHg (p < 0.001) and mean trans-valvular gradients were 6+/-3 mmHg vs 11+/-5 mmHg (p < 0.001). There were 36 patients with LV dysfunction: the results were unchanged after excluding these patients (peak gradient 12+/-6 mmHg vs. 23+/-9 mmHg, p < 0.001). Conclusions: Although TTE and TOE perform similarly prior to TAVI, the immediate post-procedural assessment of trans-aortic gradients by TOE leads to significant under-estimation compared to TTE. Intra-procedural TOE should not be used to define baseline peak and mean aortic gradients after TAVI.